New air-stable uranium(iv) complexes with enhanced volatility. (5th August 2015) - Leduc, Jennifer; Ravithas, Rajitha; Rathgeber, Lisa; Mathur, Sanjay
Abstract : New volatile uranium(iv ) complexes using a heteroarylalkenolate with an elongated fluoroalkyl chain and a tetradentate enaminone as ligands are reported. Abstract : Herein we report the synthesis and characterization of new air-stable uranium(iv ) complexes based on three different heteroarylalkenolate ligands namely DMOPFB (1) (1-(4, 5-dimethyl-oxazol-2-yl)-3, 3, 4, 4, 4-pentafluoro-but-1-en-2-ol) with an elongated fluorinated alkyl chain compared to DMOTFP (2) (3, 3, 3-trifluoro-1-(4, 5-dimethyloxazol-2-yl) propen-2-ol) and the tetradentate enaminone TFB-en (3) ( N, N ′-bis-(4, 4, 4-trifluorobut-1-en-3-on)-ethylenediamine). These new complexes exhibit sufficiently high volatilities, with respect to previously reported uranium compounds, and are thus promising precursors for chemical vapor deposition (CVD) of uranium oxide materials.